A new species of Aureonarius (Cortinariaceae, Agaricales) from Southwestern China - Fang, Yuan; Feng, Yunli; Li, Jianying; Liu, Shaoxiong; Guo, Xiang; Zhou, Fan; Ma, Ming; Hua, Rong; Sun, Dafeng (Phytotaxa, 2025)
The genus Aureonarius belongs to the family Cortinariaceae. In this study, phylogenetic inferences of Aureonarius were conducted based on sequences from a multi-locus dataset (ITS, nrLSU, RPB1, RPB2). A new species of Aureonarius discovered in Yunnan province of China was described based on morphological and molecular evidence. Aureonarius baimaensis is characterized by its medium-sized basidiomata; brownish-orange to reddish-brown tinge pileus and a pastel yellow tinge in the context; smooth central surface, with yellowish white to butter yellow finely fibrils near the edge; it typically has sterile lamella edges composed of smaller clavate cells. Morphological description, illustrations, and phylogenetic result of the new species are provided, as well as their comparisons to related taxa.